Quality management system for knowledge management inventory - Majidah Muhamad, 1984- author 610583 (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2017)
Thesis (Sarjana Kejuruteraan (Pengurusan Pembinaan))